2020
DOI: 10.1177/1557988320957545
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting the Perceived Severity of COVID-19 and HIV Infection in an Online Survey of Gay, Bisexual, and Other Men Who Have Sex With Men During the U.S. COVID-19 Epidemic

Abstract: While there is evidence of variations in the risk perceptions of COVID-19 and that they are linked to both engagement in health-protective behaviors and poor mental health outcomes, there has been a lack of attention to how individuals perceive the risk of COVID-19 relative to other infectious diseases. This paper examines the relative perceptions of the severity of COVID-19 and HIV among a sample of U.S. gay, bisexual, and other men who have sex with men (GBMSMs). The “Love and Sex in the Time of COVID-19” su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Of the twenty studies, only twelve used samples of participants consisting entirely of PLHIV. Five studies focused on MSM as a cohort and included subsamples of men living with HIV (range 7.9-17.0% of participants) [19,22,[31][32][33]36]. The results of one study are reported across two articles [32,36].…”
Section: Summary Of Social Impact Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the twenty studies, only twelve used samples of participants consisting entirely of PLHIV. Five studies focused on MSM as a cohort and included subsamples of men living with HIV (range 7.9-17.0% of participants) [19,22,[31][32][33]36]. The results of one study are reported across two articles [32,36].…”
Section: Summary Of Social Impact Studiesmentioning
confidence: 99%
“…Key editorials highlighted food insecurity and its potential association with other negative biomedical and psychosocial impacts including, non-adherence to ART, treatment interruptions and disruption to clinic visits [50,51]. Across the primary research, food insecurity was reported in six studies [19,27,28,31,32,36,45]. Santos and colleagues [19] found 20.0% of PLHIV in a global cohort study had cut or skipped meals completely, while around 40.0% of PLHIV from two US based studies experienced difficulty accessing food during the year [27,31].…”
Section: Food Insecuritymentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies centred on SGM. [42][43][44] A Taiwanese cross-sectional observational quantitative study found that sexual minorities were more likely to demonstrate health anxiety with regard to COVID-19 compared with heterosexual individuals. 42 A crosssectional US study found that most MSM believed COVID-19 could be transmitted sexually.…”
Section: Sexual and Gender Minoritiesmentioning
confidence: 99%